External Surface Water Influence on Explosive Eruption Dynamics, With Implications for Stratospheric Sulfur Delivery and Volcano-Climate Feedback - Rowell , Colin R.; Jellinek , A. Mark; Hajimirza , Sahand; Aubry , Thomas J. (Frontiers in Earth Science, 2022)
Explosive volcanic eruptions can inject sulfur dioxide (SO$_2$) into the stratosphere to form aerosol particles that modify Earth's radiation balance and drive surface cooling. Eruptions involving interactions with shallow layers ($≤$ 500 m) of surface water and ice modify the eruption dynamics that govern the delivery of SO$_2$ to the stratosphere. External surface water controls the evolution of explosive eruptions in two ways that are poorly understood: (1) by modulating the hydrostatic pressure within the conduit and at the vent, and (2) through the ingestion and mixing of external water, which governs fine ash production and eruption column buoyancy flux. To make progress, we couple one-dimensional models of conduit flow and atmospheric column rise through a novel "magma-water interaction" model that simulates the occurrence, extent and consequences of water entrainment depending on the depth of a surface water layer. We explore the effects of hydrostatic pressure on magma ascent in the conduit and gas decompression at the vent, and the conditions for which water entrainment drives fine ash production by quench fragmentation, eruption column collapse, or outright failure of the jet to breach the water surface. We show that the efficiency of water entrainment into the jet is the predominant control on jet behavior. For an increase in water depth of 50 to 100 m, the critical magma mass eruption rate required for eruption columns to reach the tropopause increases by an order of magnitude. Finally, we estimate that enhanced emission of fine ash leads to up to a 2-fold increase in the mass flux of particles $<$ 125 $μ$m to spreading umbrella clouds, together with up to a 10-fold increase in water mass flux, conditions that can enhance the removal of SO$_2$ via chemical scavenging and ash sedimentation. Overall, compared to purely magmatic eruptions, we suggest that hydrovolcanic eruptions will be characterized by a reduced delivery of SO$_2$ to the stratosphere. Our results thus suggest the possibility of an unrecognized volcano-climate feedback mechanism arising from modification of volcanic climate forcing by direct interaction of erupting magma with varying distributions of water and ice at the Earth's surface.